Sosialisasi Anti-Korupsi Sebagai Upaya Penanaman Nilai-Nilai Integritas Di Desa Barukan, Kecamatan Manisrenggo, Kabupaten Klaten - Yani Noor, Ahmad; Nur Seha, Harinto; Siswatibudi, Harpeni; Setyaningsih Sunardi, Kartika; Ainy, Nurrul; Ernawati (Jurnal Pengabdian Masyarakat Permata Indonesia, 2025)
Corruption remains a systemic problem hindering development, including at the village level. Barukan Village, Manisrenggo District, Klaten Regency, as a recipient of various village fund programs and government assistance, is vulnerable to corrupt practices if community oversight is weak. The objectives of this community service are to increase community knowledge and awareness about the dangers of corruption, introduce forms of corruption in village contexts, and motivate the community to play an active role in corruption prevention. Implementation methods used interactive lectures, group discussions, and simulations of corruption cases relevant to the village context. This activity was attended by 50 participants from various community elements. Evaluation through participatory observation showed increased understanding and participant commitment to anti-corruption values. It is concluded that anti-corruption socialization with a participatory approach is effective in increasing community awareness. For sustainability, the establishment of community anti-corruption forums and tiered socialization are needed.